Analisis Kecernaan Nutrien dan Hubungan Antar Parameter Ayam Broiler terhadap Pemberian Ekstrak Daun Bambu Apus di Bawah Cekaman Panas: Analysis of Nutrient Digestibility and Inter-Parameter Correlation on Broiler Chicken with Bamboo Leaf Extract Supplementation under Heat Stress - Lulu Sahara Wusahaningtyas; Tri Rachmanto Prihambodo; Bambang Hartoyo; Cindy Agata Pramudya; Rafli Priambodo; Delia Nurul; Wildan Nasrullah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
The objective of this study was to evaluate the effect of Bamboo leaf extract supplementation on the digestibility of dry matter, organic matter, crude protein, crude fat, and inter-parameter correlation in broiler chickens induced by heat stress. The research material used 200 unsexed broiler chickens with an average weight of 42 g. The research method used was a completely randomized design with 4 treatments and 5 replicates, namely: P0 = commercial feed, P1 = basal feed, P2 = basal feed with 1.5 g kg-1 bamboo leaf extract, and P3 = basal feed with 3 g kg-1 bamboo leaf extract. The research variables included the consumption and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), and crude fat (CF) of broiler chickens. The results showed that the addition of bamboo leaf extract had no significant effect on the digestibility of DM, OM, CP, and CR. However, the treatment with the highest extract level (P3 = 3 g kg-1) showed a better trend in DM (82.05%) and OM (46.48%) digestibility compared to other treatments. These results indicate that bamboo leaf extract has potential as a natural feed additive to support broiler chicken digestion, although the increase observed was not statistically significant. These findings are expected to serve as a basis for the development of natural ingredients in feed as an alternative to conventional additives.